LABOR TURNOVER RATE AND COST. - Prickett, A. L. (The Accounting Review, 1931)
Abstract The problem of labor turnover remains unsolved. This problem is not a new one, but over the year. has taken on varied aspects and has attained a significance which now calls for universal serious attention. The scope of the problem places it beyond the limits of comprehensive treatment in a single paper or by one individual. Of world-wide, international application, it knows no political boundaries, nor territorial prohibitions. Labor turnover is not only an industrial problem, it is a vast social problem. With some what cyclical regularity, it assumes the nature of an epidemic, under the diagnosed name of unemployment. For a single company, labor turnover has not been considered as fatal, but the effects upon business of the malady in virulent form and epidemic proportions, are paralysis or death. In 1921, consequences were serious enough to warrant coordinated and determined effort. Instead of that, only here and there was any constructive work done. No real lesson was learned. In 1929 and 1980, business suffered losses which justify the expenditure of a large sum to prevent the recurrence of such a situation or at least to insure distinct progress in that direction.